La lexicométrie historique : perspectives pour l’historiographie algérienne - Chérif Souti (Multilinguales)
In this publication, we show how Algerian historiographical research could appropriate automatic text analysis methods. We also present lexicometric methods that can be used for historical discourse analysis. We also open new research perspectives that Algerian researchers could explore in this perspective. We have carried out a contrastive lexicometric analysis of the speeches of two Algerian historical figures: Ferhat Abbas and Hadj Messali, using Hyperbase software. The lexicometric analysis, which is based on the study of lexical distance and the study of co-occurrences, reveals a dichotomous lexical reality corresponding to the political contrast between the two personalities. Indeed, F. Abbas had reformist beginnings and then progressively evolved towards nationalism, whereas M. Hadj Messali always militated for the total independence of Algeria. Our work thus shows that the borders between the two fields of research are not totally watertight and that bridges can be created in a historical-discursive perspective. Finally, it should be emphasized that the lexicostatistical approach does not claim to replace the historical approach but can complement it by opening the way to a wide range of analyses and by allowing us to work on larger corpora.